The Impact of Marketing Strategy, Product Innovation, Capital, and Operational Costs on MSME Revenue in Medan Johor District - Simbolon, Ribka Tiara Agustina; Adha , Nur Afra; Sitorus, ⁠Paskah Ria (Lembaga Riset Ilmiah, 2025)
This study aims to evaluate and examine the extent to which marketing strategies, product innovation, capital, and operational costs both individually and collectively affect the income of Micro, Small, and Medium Enterprises (MSMEs) in the Medan Johor District. This research employs a quantitative approach. The population in this study consists of all MSME actors in Medan Johor District, with a sample size of 73 MSMEs. Based on the analysis results, it was found that the four variables marketing strategy, product innovation, capital, and operational costs collectively have a significant effect on MSME income. However, when analyzed separately, only the capital variable showed a positive and significant influence on MSME income. Meanwhile, marketing strategy, product innovation, and operational costs did not exhibit a significant individual effect. The coefficient of determination test yielded an Adjusted R Square value of 0.487, indicating that 48% of the variation in MSME income can be explained by these four variables, while the remaining portion is influenced by other factors outside this study.